Pengaruh Kinerja Keuangan Terhadap Social Responsibility Perusahaan pada PT. Unilever Indonesia Tbk - Widiar Onny Kurniawan; Soffia Pudji Estiasih; Gintan Regita Maharani (JFAS : Journal of Finance and Accounting Studies, 2023)
This study has the aims of detecting the impact of ROA and ROE on CSR, the population of the financial statemenst of PT. Unilever Indonesia Tbk, sample of financial statements starting from 2018-2020 obtained 36 samples, the sampling mechanism is purposive sampling. As well as information collection techniques using documentation. Material testing using classical assumption test, multiple linear regression data analysis, hypothesis t test and F test. Based on simultaneous testing, the ROA impact on CSR is 0,000<0,05, ROE has an impact  on CSR 0,033<0,05. The implementation of better corporate social responbility can practice good things for the sustainability of the company in the long term. CSR disclosure can also show that a company is carring out its obligations properly according to existing regulations and the surrounding population and environment of the company. With the activities carried out by CSR, the company can give people confidence in the company’s products after which the good name of the company becomes excellent in the eyes of the population, and can grow financial capacity which can be shown from the ROA and ROE ratio.